2019
DOI: 10.5455/msm.2019.31.62-65
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Non-preventable Risk Factors on the Development of Osteoporosis in Postmenopausal Women

Abstract: Introduction: Scientific studies show that many genetic factors can significantly contribute to the onset of osteoporosis in women. Aim: The aim of our study was to determine whether non-preventable risk factors (certain genetic predisposition - positive parameters of family and personal history, i.e. family history of osteoporosis, family history of fractures, osteoporotic fractures, previous fractures, menopause duration) can affect the occurrence of osteoporosis in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…Non-modifiable risk factors consisted of family history, gender, age, race, and estrogen deficiency. [18][19][20][21][22][23][24][25][26] Bone mass density of postmenopausal women is highly associated with many inherited genetic matter risk factors. In various investigation, many authors suggested hereditary matters as one of the most significant hazard factors of osteoporosis.…”
Section: Non-modifiable Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-modifiable risk factors consisted of family history, gender, age, race, and estrogen deficiency. [18][19][20][21][22][23][24][25][26] Bone mass density of postmenopausal women is highly associated with many inherited genetic matter risk factors. In various investigation, many authors suggested hereditary matters as one of the most significant hazard factors of osteoporosis.…”
Section: Non-modifiable Risk Factorsmentioning
confidence: 99%
“…It is accepted that hereditary variables influence the long term bone thickness most extreme as long as 25 years old. 18 Family history of osteoporosis and fracture is highly associated with for osteoporosis risk. The record of prior fracture and family history of osteoporosis in close family members (frequently mother) are important indicators of hazard to future osteoporosis in postmenopausal women.…”
Section: Non-modifiable Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bones start losing minerals by the age 35-40 yrs of age.  Race-Osteoporosis was found to be around 20% and osteopenia in >50% in Asians and Hispanic [7]  Family History-People with family history of more likely to develop osteoporosis [8].  Body frame-Individuals with smaller body frame size are more likely to develop osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Η κορυφαία οστική μάζα καθορίζεται σε ένα ποσοστό και γενετικά. Έτσι, βρέθηκε ότι οι κόρες γυναικών που είχαν υποστεί κάταγμα ισχίου εμφάνισαν επίσης χαμηλή οστική πυκνότητα [324,325]. Επίσης παράγοντες όπως η φυσική άσκηση, η λήψη ασβεστίου και βιταμίνης D, το αλκοόλ, το κάπνισμα, η έκθεση στο ηλιακό φως και το χαμηλό βάρος σώματος, επηρεάζουν την κορυφαία οστική μάζα.…”
Section: ορισμός και κορυφαία οστική μάζαunclassified